PENGEMBANGAN SISTEM EVALUASI KINERJA DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD PADA PT. TELKOM DIVRE III - Joeliaty .; Farida Indriani (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2011)
This Research objective is to study and develop performance evaluation method in PT TelkomDivre III in accordance with well performance evaluatiob method and provide design of performance evaluation for PTTelkom Divre III.In this Research the performance evaluation method used is descriptif method using case study. According to the Analyzis, it can be concluded: Financial Perspective: Increasing of product sale and profit margin can support health financial condition .Customer Perspective: Increasing production capacity can increase product sale and customer amount, customer satisfaction and loyalty will increase profit margin. Internal Business Prosess Perspective: Increasing of productivity can increase production capacity, after sales services, time delivery and decrease production failure. Increasing after sales services can increase customer satisfaction. Increasing time delivery will increase customer satisfaction Learning and Growth Perspective: Increasing Employee Satisfaction can increase productivity.Key words: balanced scorecard, key success factors, key performance indicators, performance evaluation system, peformance measurement